1998
DOI: 10.1038/sj.leu.2400912
|View full text |Cite
|
Sign up to set email alerts
|

Estimated 6-year event-free survival of 55% in 60 consecutive adult acute lymphoblastic leukemia patients treated with an intensive phase II protocol based on high induction dose of daunorubicin

Abstract: On the basis of a previous experience suggesting that daunorubicin dose in induction was an independent prognostic factor in adult ALL, we designed a chemotherapeutic regimen (ALLVR589) characterized by high doses of daunorubicin (270 mg/m2) in induction and by high-dose Ara-C in post-remission. The protocol was otherwise conventional: induction and post-remission therapy were followed by chemo-radio prophylaxis of the central nervous system (CNS) and periodical reinductions over a 3-year maintenance period. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…25 No cardiac insufficiency occurred, confirming that idarubicin can safely replace daunorubicin. 26,27 The achievement of CR was influenced by age and cytogenetic features. 8,28 Translocation t(9;22) or BCR/ABL rearrangement decreased the CR rate (54%) as reported.…”
Section: Discussionmentioning
confidence: 99%
“…25 No cardiac insufficiency occurred, confirming that idarubicin can safely replace daunorubicin. 26,27 The achievement of CR was influenced by age and cytogenetic features. 8,28 Translocation t(9;22) or BCR/ABL rearrangement decreased the CR rate (54%) as reported.…”
Section: Discussionmentioning
confidence: 99%
“…Between October 1996 and July 2000, 377 adults with de novo ALL were registered in the GIMEMA ALL 0496 protocol (Figure 1), which was derived from the ALLVR589 regimen 9 and included patients aged 14-60 years with a diagnosis of ALL, with the exclusion of L3 B-ALL. The study was approved by the Institutional Review Board of the Department of Cellular Biotechnologies and Hematology, "La Sapienza" University of Rome.…”
Section: Design and Methodsmentioning
confidence: 99%
“…Thus, the increased dose intensity of DOX alone did not seem to contribute to the increase of CR rate in adult ALL, although the decreased dose intensity of CY might have offset the effect of increased dose intensity of DOX. Recently, Todeschini et al 15 reported 93% of CR rate using a 3-day administration of daunorubicin (DNR), and 55% 6-year EFS in adult ALL (median age, 34) employing high-dose cytarabine (Ara-C) in post-remission therapy. They used three courses of 3-day DNR (30 mg/m 2 /day) at around 3-week intervals, while we used two courses of 3-day DOX (30 mg/m 2 /day) within 10 days.…”
Section: Figurementioning
confidence: 99%
“…Although OS in the present study is not inferior to hitherto reported large-scale studies, 3,4,6,7 recent studies which include highdose Ara-C and/or high-dose MTX in the post-remission therapy report better OS. [15][16][17] Since April 2000, our National Health Insurance policy has been changed to allow us to use high-dose Ara-C. Therefore, we plan to employ high-dose Ara-C regimens in post-remission therapy in the next JALSG ALL study.…”
Section: Figurementioning
confidence: 99%